Pengaruh Budaya Asing Terhadap Penerapan Nilai – Nilai Pancasila Pada Kehidupan Remaja - Rizka Amallia; Dewi Maharani; Mulia Wulan Sari; M. Akbar Adjiguna BMY (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2024)
The term Pancasila originates from the Sanskrit word "panca" meaning five and "sila" which generally means principles. Thus, the term Pancasila refers to five fundamental principles. This research methodology employs qualitative methods, which analyze and describe with an emphasis on process and meaning in order to understand various occurrences around us by the research subjects, such as behaviors, actions, and attitudes that interpret the meaning of the data, thus aiding in understanding social life. It is essential to maintain a balance between accepting the influence of foreign cultures and preserving the values of Pancasila as the cultural identity of Indonesia. Furthermore, instilling a sense of patriotism and nationalism in the younger generation is also crucial in addressing the negative impacts of foreign cultures. Pancasila serves as the foundation of the Indonesian state and also functions as a guiding principle for society, containing the most fundamental ideas and concepts about good living. The influx of foreign cultures that alter the lifestyle and habits of society poses a significant threat to Indonesian society